Elucidation of cellular targets and exploitation of the receptor‐binding domain of SARS‐CoV‐2 for vaccine and monoclonal antibody synthesis. Issue 11 (17th July 2020) - Baig, Abdul Mannan; Khaleeq, Areeba; Syeda, Hira
Abstract: The pandemic caused by novel severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) has resulted in over 452 822 deaths in the first 20 days of June 2020 due to the coronavirus virus disease 2019 (COVID‐19). The SARS‐CoV‐2 uses the host angiotensin‐converting enzyme 2 (ACE2) receptor to gain entry inside the human cells where it replicates by using the cell protein synthesis mechanisms. The knowledge of the tissue distribution of ACE2 in human organs is therefore important to predict the clinical course of the COVID‐19. Also important is the understanding of the viral receptor‐binding domain (RBD), a region within the spike (S) proteins, that enables the entry of the virus into the host cells to synthesize vaccine and monoclonal antibodies (mAbs). We performed an exhaustive search of human protein databases to establish the tissues that express ACE2 and performed an in‐depth analysis like sequence alignments and homology modeling of the spike protein (S) of the SARS‐CoV‐2 to identify antigenic regions in the RBD that can be exploited to synthesize vaccine and mAbs. Our results show that ACE2 is widely expressed in human organs that may explain the pulmonary, systemic, and neurological deficits seen in COVID‐19 patients. We show that though the S protein of the SARS‐CoV‐2 is a homolog of S protein of SARS‐CoV‐1, it has regions of dissimilarities in the RBD and transmembrane segments. We show peptide sequences in the RBD of SARS‐CoV‐2 that can bind to the major histocompatibility complex alleles and serve as effective epitopes for vaccine and mAbs synthesis. Highlights: On the basis of our results in the present study, the distribution and density of ACE2 receptor can be computed to understand the multisystem and specific organ attacks as seen clinically in COVID‐19 caused by SARS‐CoV‐2. The expression of ACE2 in the brain provides and explanation to the neurological deficits seen in COVID‐19 as has been widely reported now. We show the emergence of mutation (99.97% sequence identities) between the SARS‐CoV‐2 (Wuhan‐Hu‐1 virus) compared with the recently deposited genomes of diverse clinical isolates (May 2020). By the homology modeling of receptor‐binding domain (RBD) of SARS‐CoV‐1 and SARS‐CoV‐2, we show the structural similarities between both the proteins. For vaccine and monoclonal antibody synthesis against SARS‐CoV‐2 we identified peptides sequences in the receptor‐binding domain (RBD) of SARS‐CoV‐2 with strong binding predictions to the MHC class I and class II allele with log‐transformed binding affinity, nM affinity, and ranks. As the amino acids in the RBD sequences predicted in this study are known to interact with human ACE2 receptors, synthesis of monoclonal antibodies against them can prove to be of translational value. Our results could be useful for designing effective prevention and treatment strategies in COVID‐19.